Characterization of food routes as potential tourist elements in rural areas. Case study: the central zone of Manabí-Ecuador - Félix Mendoza, Ángel Guillermo (2021)
Gastronomy has become one of the emblematic products of tourism, both in the heritage area of the territories and in the rural context. The objective of this research is to characterize several food routes located in the central internal zone of the province of Manabí-Ecuador. The research is exploratory, with a qualitative approach; for the characterization of the routes, certain selection criteria were established, taken from interviews with local and provincial authorities, local diagnosis sheets and a study of demand in communities were also used. Satellite georeferencing was carried out using GPS devices (Garmin Etrex 20x), these data were processed through Geographic Information Systems, specifically the Arc Gis and SAS Planet. Five representative food routes were identified in the central area of ​​the Manabí province, they have natural attractions such as rivers, river banks and waterfalls, as well as a large number of businesses associated with the concept of typical Manabí gastronomy. The rputes are located in the cantons of Chone, Bolívar, Santa Ana, Rocafuerte and Tosagua, they group 58 gastronomic establishments, the same ones that serve thousands peoples during the weekends. There is little concentration of accommodation businesses, compared to food, which clearly indicates that they are suburban destinations, which have great potential to expand their services and the stay of visitors.